A Preliminary Survey of Butterfly Diversity in Selected Districts in the Western Part of Arunachal Pradesh, India - Talukdar, Sanjay; Sarma, Hirendra N. (Indian Forester, 2010)
Study on documentation of butterfly was carried out in West Kameng, East Kameng, Lower Subansiri and Papumpare district of Arunachal Pradesh. Sampling was done from April 2004 to March 2007. Data was collected following transect method; along a 6 sections transect totaling 2km, through a variety of habitats in each district. 108 butterfly species were recorded in these districts. Different transect sections had distinct variation in butterfly number. The study areas, which belong to the western part of Arunachal Pradesh have wide range of altitudinal height ranging from 150 m to 2700 m amsl. Five lepidopteran families were recorded which include Paplionidae (15sp.), Pieridae (19sp.), Nymphalidae (56sp.), Lycaenidae (10sp.) and Hesperiidae (8sp.). Among the collected data, 60% of the species were observed as common butterflies, while 34 % uncommon and 6% rare species. Lower Subansiri district exhibited the maximum number of species, while the district of Kameng valley showed the least number.